Communication, reflexivity and harm principle: what might an ideal speech situation look like in responsibility to protect?. Issue 1 (2nd January 2020) - Piiparinen, Touko
ABSTRACT: Previous accounts of International Relations research have extensively focused on deontological ethics in analysing Responsibility to Protect (R2P). At the same time, discourse ethics – along with Jürgen Habermas' theory of ideal speech situation – has been overlooked. This article argues that the R2P process has gradually moved toward the Habermasian ideal speech situation. The Habermasian approach also provides a useful theoretical framework to understand the new, more inclusive and critical, forums of communication and initiatives set in motion by emerging non-Western norm-entrepreneurs in the R2P process, notably the Responsibility while Protecting (RwP) initiated by Brazil in 2011. From the perspective of discourse ethics, RwP could be understood as a cosmopolitan harm principle designed to manage the potentially harmful side-effects of the application of R2P. The article further argues that, despite the current paradigm shift of norm-entrepreneurship on R2P from deontological ethics to discourse ethics, it has thus far only partially fulfilled the criteria of an ideal speech situation.